La transmission de legs ottomans en Tunisie. La maisonnée Bū Ḥājib des années 1870 aux années 1930 - M’hamed Oualdi (Revue des Mondes Musulmans et de la Méditerranée)
By studying a Tunisian household, that of the Bū Ḥājib family, established in the second half of the 19th century, this essay explores the multiple forms of Ottoman legacies and the various Ottoman provincial practices used by some Tunisian elites well into the first five decades of the French colonization in Tunisia. This case study shows that families and household units – central to Ottoman society during the early modern period – remained vital to reshaping society through the action of women during the colonial period. Such an approach further reassesses an historiography whose conception was strictly colonial and focused on relations between metropolitan France and her Maghrebi colonies to the exclusion of other temporalities and Mediterranean lands and cities such as Italy, Istanbul and Cairo, all of which remained central to Tunisian people at that time.